Surveillance study on children and adolescents with Down Syndrome (3 months to 18.9 years) in the Eastern Regional Health Authority - Murphy, Joan Philomena (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Paediatrics, 2006)
Down syndrome is the most common cause of developmental disability in Ireland with a birth prevalence of 1 in 546 live births. Children with Down syndrome have a high incidence of associated treatable medical disorders. Studies have shown that early intervention carries a better medical outcome. A prerequisite for maximising medical care for those with Down syndrome is that information regarding the incidence and characteristics of their disorders together with agreed medical management guidelines are available to health professionals and policy makers. In the absence of consensus protocols for the screening and management of children and adolescents with Down syndrome in Ireland, a study was undertaken on 394 children and adolescents with Down syndrome, aged 3 months to 18.9 years in the Eastern Regional Health Authority. The purpose was to; provide medical and developmental data on Irish children and adolescents with Down syndrome; outline existing screening and management practices; and provide an evidence base to develop best practice guidelines for assessment and management. It included medical assessment of growth and development, cardiovascular, thyroid status, vision, hearing, orthopaedic and cervical spine instability, speech and language. In addition, assessment of parental concerns and quality of life issues were explored by questionnaire.
Keywords: Paediatrics, Ph.D.; Ph.D. Trinity College Dublin